PEMANTAPAN KOMPETENSI PROFESIONAL GURU KIMIA DI MGMP KIMIA SMA KABUPATEN BLITAR MELALUI PELATIHAN PEMBUATAN PERANGKAT PEMBELAJARAN BERBASIS INKUIRI - Rusly Hidayah; Sri Poedjiastoeti; Muchlis Muchlis (Universitas Negeri Surabaya, 2018)
A community service (PKM) has been in Blitar. Its objective is to describe the ability of chemistry teacher in preparing learning materials: syllabus, lesson plan and worksheet based inquiry model to train science process skills and the response of the teachers during the training activitie. Steps the activities of community service are activities undertaken refresher teacher competency and making of learning materials based inquiry model. Evaluation is done by questionnaires to participants to get the data in response to the implementation of training and marking the product of learning materials. Based on data from results of the training, it can be concluded: (1) general response chemistry teacher MGMPs in Blitar on the activities of the training is good,(2) the ability of chemistry teachers MGMP in Blitar in formulating activities based learning models of inquiry learning is good.